Determinants of job performance among administrative staffs in a private higher education institution - Thibashini, Maniam (2018)
This study examined the determinants of job performance among the administrative staffs in a private higher education institution. Specifically, the objectives were: (I) to investigate the influence of role ambiguity on job performance; (2) to determine the influence of role conflict towards job performance; (3) to examine the influence of job control towards job performance; and (4) to study the influence of organisational support towards job performance. In this cross-sectional study, 123 administrative staffs were used as sample size to conduct the study. The independent variables (i.e. role ambiguity, role conflict, job control and organisational support) and job performance was measured using standard questionnaires provided by researcher adopted from previous studies. The data obtained were analysed by using the software of Statistical Package for the Social Science (SPSS) version 21. The result showed that job performance was influenced by three variables; role ambiguity, role conflict and job control. Meanwhile, it was found through the study that organisational support does not support the hypothesis as the study showed that the organisational support is negatively related to job performance. Contributions, limitations, and implications of the study are also discussed.